Borboletas e Mariposas (Insecta: Lepidoptera) do Município de Joaçaba, Estado de Santa Catarina, Brasil - Favretto, Mario Arthur (EntomoBrasilis, 2012)
Pela primeira vez é apresentada uma lista de Lepidoptera registrados no município de Joaçaba, estado de Santa Catarina, Brasil. Os indivíduos foram coletados entre os anos de 2006 e 2010 em diferentes ambientes resultando em 58 espécies pertencentes a dez famílias. As famílias mais abundantes foram Nymphalidae e Saturniidae, representando 34,48% e 24,13% da riqueza de espécies respectivamente. Além disso, os gêneros mais representativos de Nymphalidae foram Morpho (três espécies) e Hamadryas (duas espécies), enquanto que em Saturniidae foram Rothschildia (três espécies) e Automeris (duas espécies). Butterflies and moths (Insecta: Lepidoptera) in the Municipality of Joaçaba, State of Santa Catarina, Brazil Abstract. For the first time is presented a list of Lepidoptera recorded in the municipality of Joaçaba, state of Santa Catarina, Brazil. The individuals were collected between the years 2006 and 2010 in different environments resulting in 58 species belonging to ten families. The most abundant families were Nymphalidae and Saturniidae, representing 34,48% and 24,13% of the species richness respectively. In addition, the most representative genera of Nymphalidae were Morpho (three species), and Hamadryas (two species), while in Saturniidae were Rothschildia (three species) and Automeris (two species).